The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.11604/pamj.2020.36.152.23944
|View full text |Cite
|
Sign up to set email alerts
|

The severity of fall injuries in Saudi Arabia: a cross-sectional study

Abstract: Introduction fall injuries constitute a major public health concern worldwide, contributing to over 646,000 deaths every year. The aim of this study was to determine the nature and severity of fall injuries at a tertiary hospital in the Kingdom of Saudi Arabia (KSA). Methods we conducted a cross-sectional study at the King Khalid Hospital and Prince Sultan Centre for Health Care in Al Kharj. We recruited the patients and followed them through the triage, admission and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…This trend is also observed in Jordan, where 53.7% of breast cancer patients were over the age of 50 [21] . Moreover, a multicentric, crosssectional study conducted at three hospitals in KSA from February 2019 to February 2020 reported that the risk of breast cancer increased with age in Saudi Arabia [22] . Similar findings were reported in Turkey, where Ozsoy et al noted that the risk of breast cancer increases after the age of 40 [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is also observed in Jordan, where 53.7% of breast cancer patients were over the age of 50 [21] . Moreover, a multicentric, crosssectional study conducted at three hospitals in KSA from February 2019 to February 2020 reported that the risk of breast cancer increased with age in Saudi Arabia [22] . Similar findings were reported in Turkey, where Ozsoy et al noted that the risk of breast cancer increases after the age of 40 [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Mexico found that 79% of patients had ductal histology [39] . Razik et al found that individuals in the age group of 31-45 years were less likely to be diagnosed with ductal/lobular/papillary carcinoma compared to those in the less than 30 years age group [22] . Certain histologic subtypes of breast cancer are associated with a more favorable clinical outcome, and it is important to consider histologic variety as a prognostic factor when deciding on breast cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…This underreporting is particularly evident in Asian nations, where the proportion of falls resulting in injury is significantly greater [6]. According to the Saudi Arabian Ministry of Health, over 5.42 million individuals in the country are either children or seniors [7], and falls lead to serious injuries and hospitalizations for up to half of all children and elderly persons each year [8,9]. In the Hail area, with an average hospital stay of 10.5 days and approximately 40,000 admissions per year [7], 42 hospital fall cases were reported in 2022.…”
Section: Introductionmentioning
confidence: 99%